Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

Nitrogen isotope (δ 15 N) patterns for amino acids in lemur bones are inconsistent with aridity driving megafaunal extinction in south‐western Madagascar - Sean W. Hixon; Emma A. Elliott Smith; Brooke E. Crowley; George H. Perry; Jeannot Randrianasy; Jean Freddy Ranaivoarisoa; Douglas J. Kennett; Seth D. Newsome (Journal of Quaternary Science, 2018)
Most endemic species with body masses >10 kg on Madagascar went extinct within the past 1000 years. The extent to which human predation, anthropogenic landscape transformation and aridification may separately or together explain this extinction pattern remains controversial. We present nitrogen isotope (δ 15 N) values of individual amino acids preserved in bones from now‐extinct Pachylemur insignis and extant Propithecus verreauxi from two subfossil sites in south‐western Madagascar: Tsirave and Taolambiby. The amino acid‐specific approach allows us to identify environmental signals that are otherwise difficult to recognize in bulk collagen δ 15 N values. Specifically, we use the δ 15 N values of source amino acids (phenylalanine and lysine) as a proxy for habitat aridity between ca . 4000 years ago and present and the spacing of δ 15 N values between trophic and source amino acids to quantify trophic levels for these two lemur species. Despite paleoenvironmental evidence for lowering water tables and the expansion of relatively arid savanna between 4000 and 1000 years ago, our isotope data suggest that these lemurs did not live in increasingly arid habitats and did not change their trophic level. Together, our results support the hypothesis that aridity alone did not play a major role in late Holocene megafaunal extinctions in south‐western Madagascar.

Two-Photon and Second Harmonic Microscopy in Clinical and Translational Cancer Research - Seth W. Perry; Ryan M. Burke; Edward B. Brown (Annals of Biomedical Engineering, 2012)

Adjunctive therapies for HIV-1 associated neurologic disease - Seth W. Perry; John P. Norman; Harris A. Gelbard (Neurotoxicity Research, 2005)

Tumor Necrosis Factor-Alpha in Normal and Diseased Brain: Conflicting Effects Via Intraneuronal Receptor Crosstalk? - Seth W Perry; Stephen Dewhurst; Matthew J Bellizzi; Harris A Gelbard (Journal of NeuroVirology, 2002)